Enhancing B2B Marketing in IT/Tech by Leveraging Generative AI to Drive Business Development and Branding - Veigas, Kiran (Digital Repository of Theses, 2025)
This study aims to investigate in detail the intersection between B2B marketing strategies and Generative AI. This was an entirely primary-based study, with interviews conducted in addition to an online survey sent by email to IT and Tech managers to gather primary data. LinkedIn's Professional Network was useful in locating these responders. Twenty interviewees and 200 survey respondents' data were gathered using the Purposive Sampling Technique. Using statistical tests such ordinal regression, spearman's correlation, and descriptive statistics, The SPSS program was used to assess the gathered data. Qualitative analysis revealed key terms such as "Generative", "GPT", "Genai", “Bard”, “Einstein”, “Firefly”, “Claude”, “Adobe”, "Google" and "OpenAI" in AI tools. Concerns in B2B marketing include "privacy", "ethical", “costs”, and "data security." AI tools are extensively used in "marketing", "sales", and "personalization," focusing on "content creation" and "media". In B2B marketing, terms like "business", "demand", "development", and "automation" highlight essential strategies. The study discovered statistically significant positive relationships between personalisation and customer engagement, and between Generative AI Capabilities (GAIC) and customer engagement, Data Security and Privacy (DSP) and Customer Engagement, and Augmented reality (AR) and Customer Engagement. Furthermore, Customer Engagement was found to mediate the relationship between GAIC, DSP, AR, Personalization, and Business Development and B2B Marketing Enhancement. Significant positive correlations were also found between GAIC and Business Development and B2B Marketing Enhancement, Personalization and Business Development and B2B Marketing Enhancement, DSP and Business Development and B2B Marketing Enhancement, and AR and Business Development and B2B Marketing Enhancement. The study also revealed that the company size also plays a crucial role as a control variable between these relationships. The results assert that by improving of the Generative AI Capabilities, Personalization, Data Security Privacy, and Adoption Readiness, there would be great improvement to Customer Engagement and thus Business Development and B2B Marketing. Hence, The study has significant ramifications for companies thinking about using personalisation frameworks and Generative AI Technology to increase client engagement and achieve their goals.